Стратегії сучасних лінгвістичних досліджень і завдання академічної лінгвоукраїністики (за матеріалами наукової доповіді на засіданні Президії НАН України 18 квітня 2018 р.) - Гриценко, П.Ю. (Вісник НАН України, 2018)
У доповіді окреслено стратегічні орієнтири сучасного академічного вивчення української мови, підкреслено особливу роль Національної академії наук
України не лише в науковому пізнанні усієї складності української мови в її
сучасному стані та в минулому, а й у зміні її правового поля, піднесенні
культури використання державної мови, її функціонування як інструмента освіти, культури і консолідації суспільства. Відзначено широкий міжнародний контекст дослідницьких програм мовознавців НАН України та
постійне просування результатів вивчення української мови в практику
державотворення та міжнародний науковий простір. Studies in the field of the Ukrainian language is of special significance now due to the change of language existence
model in Ukraine, the status of Ukrainian as a state language, and the widening of the spheres of its use in social communication.
Summarizing the large experience with tackling the problems of scientific support for linguistic components
of state building against the background of changing ideologies prevailing at one time or another, and the dynamics of
trends in cultural and civic life, the author proposes a set of strategic guidelines for substantial renewal of Ukrainian
language studies, both theoretical and applied ones.
He argues for the feasibility of creating a renewed and widened base of empirical linguistic data taking the form of
written and oral text corpuses and lexical databases reflecting cardinal changes in Ukrainian language text totality,
changes caused by a large amount of previously prohibited works of literature now returning to Ukrainian culture and
information space, the dissemination of texts previously existing in a single copy among their author’s papers, as well as
profound modern transformation of the stylistic means and devices of artistic, publicist and, partly, scientific discourse,
markedly on the rise from the late 1980s onwards.
Also, Ukrainian language studies acquire new significance due to the importance of this language as an element of the
Slavic and European language continuum, external influences it undergoes, and changes in active language contacts.
The change of the role of Ukrainian in the life of the state and the evolution of both its oral and written discourse require
from linguistic institutions of the National Academy of Sciences of Ukraine the systematical and comprehensive
monitoring of structural and functional transformations in this language, also calling for special attention to the problems
of interrelations between language and human and linguistic means of influencing individual and collective psyche,
and also for the in-depth study of language planning and models of language usage as connected with state security, issues
of language ecology, stability and preservation etc.